The Effect of Vanadium Oxide on The Catalytic Activity of Titanium Silicalite in Conversion of Benzene to Phenol - -, Mulyatun (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Walisongo, 2015)
Phenol is one of the most important intermediate for petrochemical, agrochemical, and plastics industries. Almost 95% phenol is produced using cumene method. Cumene method is a multi-stage process with many disadvantages including the difficulties to gain phenol product in maximum quantities and production of co-product such as acetone which has great amount in market nowadays. One of the alternative routes to produce phenol which has more advantages is through benzene hydroxylation reaction using H2O2 as oxidant agent and Titanium Silikalit-1 (TS-1) as catalyst. TS-1 catalyst has high catalytic activity and selectivity in selective oxidation reaction of aromatic compounds with H2O2 which important for commercial industries. However, the reaction rate is tend to be low because TS-1 has hydrophobic nature and as the result H2O2 adsorption which has hydrophilic nature towards active sites of TS-1 is also become slower. Addition of metal oxide V2O5 could enhance hydrophilicity of TS-1 catalyst. Liquid phase catalytic benzene hydroxylation using hydrogen peroxide as oxidant was carried out over vanadium (V) oxide-modified TS-1 catalyst (V2O5/TS-1), that were prepared by impregnation method using vanadium methavanadate as precursor and characterized by X-ray diffraction, infrared spectroscopy, nitrogen adsorption, pyridine adsorption, and hydrophilicity techniques